The influence of awareness, knowledge, and environmental culture on MSME tax compliance with tax administration modernization and tax incentives as moderating variables - Delia, Delia; Rachmat, Radhi Abdul Halim (Educoretax, 2025)
This study aims to analyze the effect of Taxpayer Awareness, Tax Knowledge, and Environmental Culture on the Tax Compliance of MSMEs in Bandung City, with Tax Administration Modernization and Tax Incentives as moderating variables. This quantitative research used a survey method involving individual MSME taxpayers registered at the Pratama Tax Service Office in Bandung. The data analysis employed multiple linear regression and Moderated Regression Analysis (MRA), processed using SPSS 25. The results revealed that Awareness, Tax Knowledge, and Environmental Culture significantly influence MSME Tax Compliance. However, the moderating variables—Tax Administration Modernization and Tax Incentives—did not strengthen those relationships. These findings highlight that internal and social factors are more dominant in shaping tax compliance behavior, while technological modernization and fiscal incentives are yet to be effective drivers. This research contributes to the formulation of more targeted tax policies for MSMEs in Indonesia.